Building Coalitions: Communication/Developing Members - Jeffrey King; Kathryn Beckham; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY498, Part 6 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.